2014
DOI: 10.5812/cardiovascmed.25173
|View full text |Cite
|
Sign up to set email alerts
|

Persistent isolated right atrial standstill associated with left atrial tachycardia

Abstract: Introduction:Atrial standstill is a rare condition, characterized by absence of atrial electrical and mechanical activity evident in surface electrocardiography echocardiography, or fluoroscopy, which is associated with unresponsiveness of atria to maximal output electrical stimulation. This condition can be present with thromboembolic complication, low cardiac output, and sometimes palpitation.Case Presentation:Here we presented a woman with right atrial stand still and left atrial tachycardia. It was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Prior cases of AS have been reported in the adult literature with tachyarrhythmias in Brugada syndrome due to SCN5A mutation and catecholeminergic polymorphic ventricular tachycardia associated with RYR2 mutation. 4 , 5 Jorat et al 6 reported a case of isolated right AS with left atrial tachycardia in a 32-year-old female patient. Like our patient, she presented with chronic fatigue and dyspnea suggestive of bradycardia and a progressive course.…”
Section: Discussionmentioning
confidence: 99%
“…Prior cases of AS have been reported in the adult literature with tachyarrhythmias in Brugada syndrome due to SCN5A mutation and catecholeminergic polymorphic ventricular tachycardia associated with RYR2 mutation. 4 , 5 Jorat et al 6 reported a case of isolated right AS with left atrial tachycardia in a 32-year-old female patient. Like our patient, she presented with chronic fatigue and dyspnea suggestive of bradycardia and a progressive course.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial standstill is a rare arrhythmia defined by the absence of mechanical and electrical activity in the atria. It was first described in 1946 by Chavez et al 1 The diagnostic criteria include: (a) abnormal or absent P-waves in surface and intracavity electrocardiograms (ECGs). If present, atrial activity is slow and erratic, with a prolonged, low-amplitude and low-frequency electrogram; (b) evidence of atrial asystole, that is, the absence of A-waves in jugular venous pulse and right atrial pressure tracings; (c) supraventricular QRS morphology; (d) immobility of the atria on fluoroscopy and (e) inability to stimulate the atria electrically.…”
Section: Introductionmentioning
confidence: 99%
“…If present, atrial activity is slow and erratic, with a prolonged, low-amplitude and low-frequency electrogram; (b) evidence of atrial asystole, that is, the absence of A-waves in jugular venous pulse and right atrial pressure tracings; (c) supraventricular QRS morphology; (d) immobility of the atria on fluoroscopy and (e) inability to stimulate the atria electrically. 25 Few cases of atrial standstill have been described in children. 69 We report a case of atrial standstill in a 7-year-old girl presenting with cerebral infarction with expressive aphasia and central facial palsy.…”
Section: Introductionmentioning
confidence: 99%